2018
DOI: 10.1093/ajcp/aqy084
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cervical Neoplasia by Human Papillomavirus Testing in an Atypical Squamous Cells-Undetermined Significance Population

Abstract: ObjectivesTo determine clinical utility of Onclarity human papillomavirus (HPV) assay for atypical squamous cells-undetermined significance (ASC-US) triage, and the value of HPV genotyping within ASC-US.MethodsWomen (n = 33,858; 21 years or older) had HPV testing using Onclarity and Hybrid Capture 2 (HC2). ASC-US individuals (n = 1,960, 5.8%) were referred to colposcopy.ResultsOf ASC-US, 39.1% were HPV positive by Onclarity; HPV 16 was the most prevalent genotype (7.4%). Cervical intraepithelial neoplasia grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Of the 33,858 screened patients, 224 were excluded due to nonevaluable cytology. Of the remaining 33,634 specimens, those with ASC-US or higher (n = 3,082) were discussed in Wright et al, 33 and a further 63 with unsatisfactory cytology were not included in the current analysis. Likewise, 8,106 patients were younger than 30 years, leaving 22,383 patients, 30 years or older, with a NILM cytology result.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 33,858 screened patients, 224 were excluded due to nonevaluable cytology. Of the remaining 33,634 specimens, those with ASC-US or higher (n = 3,082) were discussed in Wright et al, 33 and a further 63 with unsatisfactory cytology were not included in the current analysis. Likewise, 8,106 patients were younger than 30 years, leaving 22,383 patients, 30 years or older, with a NILM cytology result.…”
Section: Methodsmentioning
confidence: 99%
“…The design of the Onclarity HPV trial has been described previously in depth [8,15,16]. In brief, 33,858 subjects, ≥21 years, undergoing routine cervical cancer screening were recruited at 31 clinical sites in 17 states.…”
Section: Study Design and Enrollment Visitmentioning
confidence: 99%
“…This approach reduces the number of colposcopies that are performed by approximately 50%, however, most HPV positive women with ASC-US who are referred to colposcopy do not have ≥CIN3. Five U.S. regulatory studies of different HPV diagnostic tests have reported that risk stratification of women with ASC-US by HPV testing (pooled high-risk genotypes) refers 32.6%-57.1% to colposcopy and identifies 87.5%-100% of ≥CIN3 lesions [4][5][6][7][8]. The positive predictive value for ≥CIN3 of HPV testing (pooled high-risk genotypes) ranged from 2.9%-9.4%.…”
Section: Introductionmentioning
confidence: 99%
“…The BD Onclarity™ HPV Assay provides results on an automated platform (BD Viper LT™ System) and offers genotyping with individual reporting of types 16, 18, 31, 45, 51 and 52 and identification of three groups of types: 33/58, 56/59/66 and 35/39/68. The Onclarity HPV test is internationally validated on both SurePath and Thinprep LBC media for use in primary HPV screening and has recently received FDA approval for primary screening in women over 25 years in the United States . To investigate the risk of disease arising from the individual HPV genotypes, we used Bayesian data analysis which provides a natural and principled way of modeling risk in subjects with multiple genotype infections.…”
Section: Introductionmentioning
confidence: 99%
“…The Onclarity HPV test is internationally validated on both SurePath and Thinprep LBC media for use in primary HPV screening 14,15 and has recently received FDA approval for primary screening in women over 25 years in the United States. 16,17 To investigate the risk of disease arising from the individual HPV genotypes, we used Bayesian data analysis which provides a natural and principled way of modeling risk in subjects with multiple genotype infections.…”
Section: Introductionmentioning
confidence: 99%